Relationship between Sputum Bacilloscopy and Radiological Lesions in Pulmonary Tuberculosis (Bangladesh Journal of Medical Science, 2026)
Background Pulmonary tuberculosis (PTB) is still a major public health concern worldwide, especially in developing countries. The detection of acid-fast bacilli (AFB) through sputum bacilloscopy in respiratory specimens is the cornerstone for diagnosing active PTB. This study aims to evaluate the relationship between sputum bacilloscopy results and radiological lesions in patients with pulmonary tuberculosis. Methods This observational study was carried out in the Department of Internal Medicine, Bangladesh Medical University (BMU), Dhaka, Bangladesh, from 1st January 2015 to 31st January 2016. Seventy (70) newly diagnosed PTB patients attending the inpatient and outpatient departments were recruited prior to initiation of anti-TB chemotherapy. The Data were manually processed and analyzed using the Statistical Package for the Social Sciences version 21. Result The average age of 70 pulmonary tuberculosis patients was 34.3 years with male is slightly higher than female (55.7%). Most had normal BMI, though low BMI was more frequent among PTB cases. Cough (92.5%), fever (68.5%), and weight loss (60%) were the most common clinical symptoms. Hematological analysis revealed mild anemia and elevated ESR. Sputum AFB was positive in 45.7% and GeneXpert in 75.7%. Chest X-rays showed consolidation in 50% and cavitation developed in 40% of patients. There was a significant association of AFB positivity with consolidation and cavitary lesions (p < 0.05). Conclusion This study demonstrates a definite association between sputum bacilloscopic and radiological lesion in pulmonary tuberculosis. Consolidation and cavitary lesions were significantly more frequent among smear-positive patients, reflecting a higher bacillary load and more extensive pulmonary involvement.BJMS, Vol. 25 No. 01 January’26 Page : 263-268